2014
DOI: 10.1002/2014jb011151
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically modeling fault step overs using various friction laws

Abstract: It is well known that fault step overs can under some circumstances allow through-going rupture and under other circumstances cause rupture to terminate. However, the effects of different friction law formulations on jumping rupture have not been extensively explored. In this study we use the 2-D dynamic finite element method to investigate how different frictional parameterizations affect the ability of rupture to jump a step over, in both extensional and compressional settings. We compare linear slip-weakeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 78 publications
3
53
0
Order By: Relevance
“…In both cases, static stresses alone are not sufficient to breach the step over because of their relatively small amplitude compared with dynamic stresses. A slightly larger compressional step over jump than a dilational one is also observed in most of the examples presented by Hu et al () and in some of the cases in Lozos et al () and Ryan and Oglesby (), especially in the sub‐Rayleigh rupture cases. This implies that the step over distance H c can be underestimated if only static stress are considered, especially for a compressional step over.…”
Section: Simulation Resultssupporting
confidence: 57%
“…In both cases, static stresses alone are not sufficient to breach the step over because of their relatively small amplitude compared with dynamic stresses. A slightly larger compressional step over jump than a dilational one is also observed in most of the examples presented by Hu et al () and in some of the cases in Lozos et al () and Ryan and Oglesby (), especially in the sub‐Rayleigh rupture cases. This implies that the step over distance H c can be underestimated if only static stress are considered, especially for a compressional step over.…”
Section: Simulation Resultssupporting
confidence: 57%
“…[] also noticed the occurrence of supershear rupture on an extensional step over. Based on 2‐D numerical simulations, Ryan and Oglesby [] found that ruptures across step overs could lead to a supershear transition and showed that the minimum step width required for sustained supershear ruptures on compressional regimes obeying linear slip‐weakening law was 0.6 km if the initial S value was 2.6 on the step overs. However, according to the critical jump distance study by Hu et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, earthquake ruptures involve high slip rates at which microscopic asperities in the thin slip zone may experience transient heating that thermally weakens the frictional strength. A modified model based on rate‐ and state‐friction to better fit this flash heating phenomenon is proposed (Beeler et al, ; Rice, , ) and applied in rupture modeling (e.g., Rojas et al, ; Ryan & Oglesby, ). In this model, the steady state friction coefficient f ss defined in the RS‐S law is retained for low slip rate condition and is renamed low‐velocity steady state friction coefficient f LV .…”
Section: Functional Forms Of Various Friction Lawsmentioning
confidence: 99%
“…The stress‐slip curves for the RS‐S and RS‐FH laws, however, show an exponentially decaying pattern as the shear stress gradually evolves from the yield strength to the dynamic friction with respect to the slip. One way to compare this group with the linearly weakening group is to compare fracture energy among all the friction laws (Ampuero & Rubin, ; Ryan & Oglesby, ), since the fracture energy is critical for self‐sustaining rupture propagation and determines rupture speed (Fukuyama & Madariaga, ). As a lumped parameter representing all kinds of energy dissipated in the cohesive zone, the fracture energy is defined as the work done against the friction excess [ τ ( δ ) − τ d ] over the critical distance d 0 : gc=0d0[]τ()δτditalicdδ where τ ( δ ) is the friction as a function of slip.…”
Section: Comparing Frictional Behaviors Of Various Friction Lawsmentioning
confidence: 99%